Distance Learning during Pandemic: A Review of New Challenges and Opportunities for Educational Refinements in Indonesia - Madjid, Abd.; M. Suud, Fitriah; Bahiroh, Siti (CV. Creative Tugu Pena, 2023)
Changes that arise due to the coronavirus afflict all sides of life. One of the new problems is the change in learning methods from face-to-face to distance learning. This study aimed to analyze the new challenges and opportunities that arise from the distance learning process during the Covid 19 pandemic in Indonesia. The research method used to collect data is through academic search engines at several specific literacy sources in Indonesia, given a deadline of 2020. The data analysis used is the content analysis paradigm with the presentation in linguistic formulations. This review found that Indonesian learners learn very quickly by means of self-regulated learning. The integration pattern of teachers, students and parents is the way to solve problems from online learning. Student creativity and independence are new opportunities for students in Indonesia. Keywords: Distance Learning, Educational Refinements, Learning at Pandemic